Clinical outcomes from out-of-hospital cardiac arrest in low-resource settings — A scoping review. (November 2020) - Schnaubelt, S.; Monsieurs, K.G.; Semeraro, F.; Schlieber, J.; Cheng, A.; Bigham, B.L.; Garg, R.; Finn, J.C.; Greif, R.; ,; Bray, Janet; Breckwoldt, Jan; et al.
Abstract: Aim of the scoping review: Scientific recommendations on resuscitation are typically formulated from the perspective of an ideal resource environment, with little consideration of applicability in lower-income countries. We aimed to determine clinical outcomes from out-of-hospital cardiac arrest (OHCA) in low-resource countries, to identify shortcomings related to resuscitation in these areas and possible solutions, and to suggest future research priorities. Data sources: This scoping review was part of the continuous evidence evaluation process of the International Liaison Committee on Resuscitation (ILCOR), and was performed following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. We identified low-resource countries as countries with a low- or middle gross national income per capita (World Bank data). We performed a literature search on outcomes after OHCA in these countries, and we extracted data on the outcome. We applied descriptive statistics and conducted a post-hoc correlation analysis of cohort size and ROSC rates. Results: We defined 24 eligible studies originating from middle-income countries, but none from low-income regions, suggesting a reporting bias. The number of reported patients in these studies ranged from 54 to 3214. Utstein-style reporting was rarely used. Return of spontaneous circulation varied from 0% to 62%. Fifteen studies reported on survival to hospital discharge (between 1.0 and 16.7%) or favourable neurological outcome (between 1.0 and 9.3%). An inverse correlation was found for study cohort size and the rate of return of spontaneous circulation ( ρ = −0.48, p = 0.034). Conclusion: Studies of OHCA outcomes in low-resource countries are heterogeneous and may be compromised by reporting bias. Minimum cardiopulmonary resuscitation standards for low-resource settings should be developed collaboratively involving local experts, respecting culture and context while balancing competing health priorities.